Liang-Ge-San, a classic traditional Chinese medicine formula, attenuates acute inflammation in zebrafish and RAW 264.7 cells. (1st March 2020) - Zhou, Hongling; Cao, Huihui; Zheng, Yuanru; Lu, Zibin; Chen, Yuyao; Liu, Dongyi; Yang, Huayi; Quan, Jingyu; Huo, Chuying; Liu, Junshan; Yu, Linzhong
Abstract: Ethnopharmacological relevance: Liang-Ge-San (LGS) is a traditional Chinese medicine formula that commonly used in acute inflammatory diseases. However, the anti-inflammatory effects and the underlying mechanisms of LGS are not fully studied. Aim of the study: This study aims to investigate the anti-inflammatory activity and explore the underlying mechanisms of LGS in zebrafish and cell inflammation models. Materials and methods: LPS-induced zebrafish inflammation model was established by LPS-yolk microinjection. The protective effect of LGS on zebrafish injected with LPS was observed using survival analysis. Infiltration of inflammatory cells was determined by H&E staining assay. Expression levels of key inflammatory cytokines TNF-α and IL-6 were measured by q-PCR assay. Recruitment of neutrophils and macrophages were observed by fluorescence microscopy, SB staining and NR staining. In vitro anti-inflammatory effects of LGS were evaluated on LPS-stimulated RAW 264.7 cells. The generation of IL-6 and TNF-α was detected by ELISA. The protein expression levels of JNK, p-JNK (Thr183/Tyr185), Nur77 and p-Nur77 (Ser351) were determined by Western blotting. Finally, two additional inflammatory models in zebrafish, which were induced by CuSO4 or tail fin injury, were also established and the recruitment of neutrophils and macrophages were observed for the determination of the anti-inflammatory activity of LGS. Results: LGS protected zebrafish against LPS-induced death and dose-dependently inhibited LPS-induced acute inflammatory response in zebrafish, as indicated by increased survival rate, reduced infiltration of inflammatory cells, decreased recruitment of macrophages and neutrophils, and downregulated expression levels of TNF-α and IL-6. Additionally, LGS inhibited the secretion of TNF-α and IL-6, increased the expression of Nur77, and reduced the expression of p-Nur77 (Ser351) and p-JNK (Thr183/Tyr185) in LPS-stimulated RAW 264.7 cells. The anti-inflammatory action of LGS was also observed in another two zebrafish inflammation models, which was supported by the inhibition on neutrophils and macrophages recruitment. Conclusion: The present study demonstrates that LGS possesses anti-inflammatory activity in zebrafish inflammation models and LPS-stimulated RAW 264.7 cells, which is related to the inhibition on p-JNK and p-Nur77. This finding provides a pharmacological basis for LGS in the control of inflammatory disorder. Graphical abstract: Image 1